РЕТРОСПЕКТИВНИЙ АНАЛІЗ ПІЗНАВАЛЬНОЇ АКТИВНОСТІ ЯК ФІЛОСОФСЬКОЇ ПРОБЛЕМИ (Педагогіка вищої та середньої школи, 2022)
In clause the author traces development of concepts "cognitive" and "cognitive activity99 in philosophical sources. The modem philosophical approaches to interpretation of the term "cognitive activity99 are opened.